Practices of SHS Faculties in Handling Student’s Behavior in Classroom toward an Intervention Program (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Education plays a crucial role in the progress of any nation and is vital for human development and a country’s transformation. Every teacher should perform functions to create a wholesome atmosphere in the school community by considering the students’ behavior toward their school life, such as academic work, discipline, interpersonal relationships, and belongingness to school. If these things are provided for, then positive behavior toward the achievement of student’s academic goals in their studies and their social competence toward others will be enhanced and developed. This study used mixed methods and quantitative and qualitative research and used the purposive sampling technique in choosing where the study should be conducted. The research subjects of this study were 25 senior high school faculties at Bestlink College of the Philippines. The result of this study showed that most of the SHS faculties used encouragement, recognition, and specific feedback regarding behavior and expectation as to their practices in handling students’ behavior in the classroom; it had a weighted mean of 4.32, with an interpretation of "often." This study showed that parents, students, and teachers must attend a seminar that provides knowledge on how to improve the behavior of young people. Inside the classroom, teachers should maintain the consistency of the rule implemented. At home, parents should give their attention and show their affection to their children. Administrators must ensure that all learning nurtures and protects the special bonds that develop among teachers, students, principals, and families who work together for the common good of our school.
Keywords: behavior, emotional problem, intervention program, discipline, behavioral problem